Practical ways for coaches to reduce their stress and avoid burnout - Robert Pearson; Timothy Baghurst (Acta Universitatis Carolinae: Kinanthropologica, 2020)
Stress and the potential for burnout are a very real and present concern for coaches at all levels of competition. However, while stress is ever-present, many coaches have never received education or training on how to effectively cope with experienced stress. Therefore, the purpose of this article is to present practical ways for coaches to reduce stress and avoid burnout. A brief review of stress, burnout, and the stressors coaches often face are presented. This is followed by methods to help mitigate stress and avoid burnout including best practices for physical activity, meditation, connecting with mentors, connecting with family, renewal, setting limits, saying no, continuing education, and some unexpected methods to reduce stress. All coaches will experience stress, and its recognition, combined with the skills and tools needed to moderate its effects aid in longer and more successful coaching careers.